PERSEPSI ANALIS KREDIT / PEMBIAYAAN TENTANG RESIKO KREDIT PADA BANK KONVENSIONAL DAN BANK SYARIAH (STUDIKASUS PADA BANK CENTRAL ASIA DAN BANK SYARIAH MANDIRI) - Samiah Harhara; Sofyan S Harahap (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
A number of theories on Islamic accounting have been proposed in the study on Islamic accounting. It has been showed that there is a require for Moslem business organization to have a different accounting that build successful for Muslim, not only in this life but also for hereafter. This study attempts to elaborate the perception on credit analysis in Islamic banking and in conventional banking in Jakarta. There are three hypotheses that has been examined. The result shows that there is no significant perception difference among the two on